Deuterium z-pinch as a powerful source of multi-MeV ions and neutrons for advanced - Klír, D.; Shishlov, A. V.; Kokshenev, V. A.; Kubeš, P.; Řezáč, K.; Cikhardt, J.; Cikhardtová, B.; Kravárik, J. (AIP Publishing, 2016)
A novel configuration of a deuterium z-pinch has been used to generate a nanosecond pulse of fast ions and neutrons. At a 3 MA current, the peak neutron yield of (3.6 ± 0.5) × 1012 was emitted within 20 ns implying the production rate of 1020 neutrons/s. High neutron yields resulted from the magnetization of MeV deuterons inside plasmas. Whereas deuterons were trapped in the radial direction, a lot of fast ions escaped the z-pinch along the z-axis. A large number of >25 MeV ions were emitted into a 250 mrad cone. The cut-off energy of broad energy spectra of hydrogen ions approached 40 MeV. The total number of >1 MeV and >25 MeV deuterons were 1016 and 1013, respectively. Utilizing these ions offers a real possibility of various applications, including the increase of neutron yields or the production of short-lived isotopes in samples placed in ion paths. On the basis of our experiments with various samples, we concluded that a single shot would have been sufficient to obtain GBq positron activity of 13N isotopes via the 12C(d,n)13N reaction. Furthermore, the first z-pinch generated neutron radiograph produced by ≈20 ns pulses is presented in this paper.